Librarian and scientist Kazys Sendzikas - Genovaitė Raguotienė (Knygotyra)
Two articles discuss the research of Kazys Sendzikas (1909?-1940) on Lithuanian libraries and the history of the period of the Republic (1918-1940). First, the author reviews Sendzikas's written heritage, which consists of 20 items. These are mainly articles on Lithuanian library history, particularly on the Library of the Kaunas Priests' Seminary. K. Sendzikas prepared publications from the archives and manuscripts departments on Lithuanian books and authors of the first half of the 19th century. These materials cover famous cultural, library, and book workers such as M. Valančius, J. K. Gintila, J. A. Pabrėža, B. Šmigelskis, and others. The author analyzes Sendzikas's studies on parish libraries, reading, and archives.